Ethnomatematics of South Bengkulu in Mathematical Learning Community - Ginta Octizasari; Saleh Haji (SAINTIS Publishing, 2019)
The purpose of this study was to Determine the implications of the results of this study on learning mathematics. The research of data were Obtained from observations, interviews with traditional South Bengkulu cake sellers, and interviews with mathematics teachers. The results Showed that various research activities Showed that the elements of mathematics in cultured activities could be implicated in mathematics learning items, namely looking for Certain patterns to Determine the elements in the circle and activities by using cultured Contexts students could find concepts in finding the circle area circle. Students' activities in finding concepts can develop critical and creative thinking and can improve the character of love in the local culture. So that teaching materials using cultural Contexts can be practiced and developed in mathematics learning in junior high schools (SMP) in the 2013 curriculum. This study produces a mathematical syntax with ethnomatematics learning approach.